Instituição, ideia e conhecimento: análise do processo de implementação do programa de ação afirmativa na Universidade Federal de Sergipe (2001-2008) - Mamede, Zoraide Vasconcelos (2014)
The intention of this study was to discuss the dynamics, institutional conditions and subjective factors that influenced the actors to legitimize the policy of affirmative action in the Federal University of Sergipe. Specifically, treated to investigate how certain dynamics of an institution influence the actors to position themselves somehow in defense of public policy. This involves analyzing how state and society relate to processes of implementation of public policies, focusing on analysis of the process that culminated in the Affirmative Action Program of the Federal University of Sergipe. This research is embedded in a more general problem that relates institutional patterns, the weight of beliefs, ideas and expertise of the actors involved in the processes of construction of public policy. At first, problematized up the affirmative action policies based on the investigation of its emergence in Brazil, using the notion of |path dependence| and showed that even the unprecedented initiatives in terms of public policy, arise from the motivations and opportunities provided by the institution itself. As a result, it was important to analyze the moments of institutional change, through an historical mapping that identified conflicts that permeated institutions. Subsequently, the intention was to demonstrate that the process of public policy formulation sets up the coordinated action of several actors, but mainly it is the interaction of ideas and beliefs that characterizes the process (policy process). Ordinarily, studies applying the analytical approach of the |Advocacy Coalitions| model attempt to show how the competing coalitions compete in a given subsystem by the success of the policy. It turns out that, when applying this approach to the study at hand, it was found that the process of implementation of the UFS resulted in the formation of a coalition only defense. The ideas here have had a significant weight when they were articulated with technical knowledge. The analysis of this case showed that 1.the rules and regulations of the institution had great weight in the development of this policy in the UFS, as they found the formation of a coalition only defense of quotas; 2. the defense of quotas coalition remained united by the belief system that was translated in Program of the Federal University of Sergipe, thus ensuring the success of the policy; 3. the technical knowledge had influence over policy decisions in the UFS, as this process gained legitimacy from the results of studies and surveys of teachers involved in the construction of this policy at university.